PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA MELALUI INOVASI PEMBELAJARAN TERINTEGRASI SITUS PURBAKALA CANDI MUARO JAMBI BERBASIS ADOBE FLASH - Salam, M.; Dani, Rahma; Mustofa Meihan, Andre (Edu Sosial, 2023)
This research aims to improve students' critical thinking skills in the class A Civics Education Study Program in the odd semester Pancasila course. This type of research is classroom action research. This research uses 3 cycles and each cycle has 4 stages, namely Planning, Action, Observation and Reflection. The research results show that there has been an increase in students' critical thinking skills through integrated learning innovations at the Muaro Jambi Temple Archaeological Site based on Adobe Flash. In cycle 1, students obtained an average critical thinking ability score of 47 with a percentage of 58.75% and were included in the good category. In Cycle II, students' thinking ability scores reached an average of 55.79 or a percentage of 69.73%. This score shows that students have good critical thinking skills and have experienced an increase in scores from cycle I. In Cycle III students have received an average critical thinking ability score of 65.07 or a percentage of 81.33%. Students' critical thinking abilities in cycle III have entered the very good category. After carrying out cycle III, the indicators of success have been achieved so that this research can be declared successful.